Risk communication : a handbook for communicating environmental, safety, and health risks - Lundgren, Regina E., 1959-; McMakin, Andrea H., 1957- (Hoboken, New Jersey : IEEE Press/Wiley, 2013)
This fully-updated fifth edition includes real-life examples of current events such as the Japanese tsunami, the Gulf oil disaster, and Hurricane Irene, along with lessons learned from these events. The coverage also includes new chapters on public health campaigns, and on the use and effectiveness of social media such as blogging, video, and image sharing for risk communication purposes. Combing sound, scientific research with practical advice in an accessible format, this book is a must-read for practitioners, engineers, scientists, and public health agencies.
Communicate Honestly, Clearly, and Compassionately.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Risk communication -- Handbooks, manuals, etc; BUSINESS & ECONOMICS -- Development -- Sustainable Development; Risk communication; Communication; Risk communication -- Handbooks, manuals, etc; Risk factors; Electronic books; Handbooks and manuals; Electronic books